Compression characteristics of Andrographis paniculata herbal plant extract. - Abdul Razak, Norawanis (2010)
This study was conducted to investigate tablet formulation of Andrographis paniculata extract powder by direct compression in a 13mm-diameter-cylindrical unaxial die in two different amounts of feed, 0.5 and 1.0g. The tablets were formed using microcrystalline cellulose and k-carrageenan as binders. The compression pressure was varied between 7.5 to 73.8 MPa. Kawakita and ludde (1970/71) and Heckel (1961) models were selected to validate the experimental data. The objectives were to (i) examine the compressibility of Andrographis paniculata in the presence of binders (ii) validate the data with established models that describes the compression, and (iii) determine their optimum operating conditions. Compression characteristics were evaluated using density-pressure and tensile strength-volume reduction relationships. The tablet characteristics including tensile strength, ejection force, friability and dissolution time, were analyzed on different amounts of Andrographis paniculata and binders. The tensile strength was positively related to the volume reduction, tablet’s density and applied pressure during compression. This study showed that microcrystalline cellulose had better binder quality compared to k-carrageenan in direct compression of Andrographis paniculata tablet. The shape, size and quantity of the feed powders greatly affected to the particle arrangement during compression. The optimum condition and formulation for Andrographis paniculata tablet at 0.5g of feed powder was 10 to 30% microcrystalline cellulose at 37.7 to 73.8 MPa pressure. However, at 1.0g of feed powder, the best formulation was 30% microcrystalline cellulose at 52.7 to 73.8 MPa pressure. When k-carrageenan was used as a binder, the best formulation was 10% k-carrageenan at 73.8 MPa pressure. The k-carrageenan can be used in pharmaceutical tablet manufacturing because of its health benefits and much lower price compared to microcrystalline cellulose. This data for tablet processing may contribute to the development of herbal tablet industry in Malaysia.